Generation of University Spin Off Companies: Challenges from Mexico - Pérez-Hernández,Pilar (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2021)
Abstract Spin off companies refer to firms created by university laboratories, the generation of this type of companies has a pull effect through the diffusion, imitation and innovation of the company even at long-term for economic development. In order to generate this type of business, an articulated set of legislative, cultural and financing, instruments are required. In addition, various actors must be involved; aligned to achieve local development. The ability of universities to create spin off companies depends on their background and favorable regional conditions. This research aims to identify the main challenges during spawn university spin off companies in Mexico, thus, it is necessary explore the consequences and analyze key factors of entrepreneurial university scheme, at the end of this paper illustrates Mexico’s outlook and the conclusions. There are four major challenges that universities faces: first, the lack of clear and effective internal regulations and paperwork processes for intellectual property management and proper commercialization strategies for technological developments; second, is not hiring specialists for Technology Transfer Offices at Higher Education Institutes (HEI) and Public Research Centres (PRC) to generate capabilities; third, inherent complexities of business training and entrepreneurship education, to enhance management competences and business venture, and fourth, decision-maker authority at HEIs and PRCs must develops an enabling environment as governance mechanisms that support and prioritize such processes, so that could be translated into punctual actions with concrete results.